2021
DOI: 10.3390/en14248243
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Inhibition and Flow Improvement of Crude Oil with a High Content of Asphaltene and Wax by Polymers Bearing Ultra-Long Side Chain

Abstract: A high content of asphaltene and wax in crude oil leads to difficulties in the recovery and transportation of crude oil due to the precipitation of asphaltenes and the deposition of waxes. Comb-like polymers were found to be capable of inhibiting the aggregation of asphaltenes and crystallization of waxes. In this work, comb-like bipolymers of α-olefins/ultra-long chain (C18, C22 and C28) alkyl acrylate were synthesized and characterized by FT-IR and 1H NMR spectra. The results show that, for a model oil conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, a high API gravity does not necessarily mean that SWA treatment will be highly effective for oil removal as it is affected by various factors. High wax and asphaltene content can make light oils become difficult to remove and recover because of wax deposition and asphaltenes precipitation (Li et al, 2021). In real oil spill scenarios, it usually takes some time from the occurrence of an oil spill to the time when the spilled oil is cleaned up, so the stranded oil will undergo a series of weathering processes, such as evaporation, emulsification, oxidation, and biodegradation, leaving high percentages of large and recalcitrant components (Ossai et al, 2020;Bi et al, 2022b).…”
Section: Chemical Treatment For Light Oilsmentioning
confidence: 99%
“…However, a high API gravity does not necessarily mean that SWA treatment will be highly effective for oil removal as it is affected by various factors. High wax and asphaltene content can make light oils become difficult to remove and recover because of wax deposition and asphaltenes precipitation (Li et al, 2021). In real oil spill scenarios, it usually takes some time from the occurrence of an oil spill to the time when the spilled oil is cleaned up, so the stranded oil will undergo a series of weathering processes, such as evaporation, emulsification, oxidation, and biodegradation, leaving high percentages of large and recalcitrant components (Ossai et al, 2020;Bi et al, 2022b).…”
Section: Chemical Treatment For Light Oilsmentioning
confidence: 99%
“…Some studies indicate that asphaltenes can lower the WAT of oils. Tinsley et al asserted that the introduction of asphaltenes reduces the temperature of wax crystallization, a phenomenon unaffected by asphaltene concentration but progressively attenuating with increasing wax content. Similar findings have been corroborated by Li et al, emphasizing that asphaltenes and compatible pour point depressants perform analogous functions, both significantly reducing the WAT. In addition, Ruwoldt et al found that both PPD and asphaltene had similar abilities to reduce WAT, but there was no direct correspondence between them.…”
Section: Introductionmentioning
confidence: 99%
“…However, research regarding the impact of asphaltenes on WAT has hitherto lacked a consistent consensus. Some studies indicate that asphaltenes can lower the WAT of oils. Tinsley et al asserted that the introduction of asphaltenes reduces the temperature of wax crystallization, a phenomenon unaffected by asphaltene concentration but progressively attenuating with increasing wax content. Similar findings have been corroborated by Li et al, emphasizing that asphaltenes and compatible pour point depressants perform analogous functions, both significantly reducing the WAT.…”
Section: Introductionmentioning
confidence: 99%
“…and polymer-based asphaltene dispersants (e.g., nonpolymer alkyls of polymethacrylate, comb-like polymers, etc.). Salicylic acid, phthalic acid, benzoic acid, dodecyl benzenesulfonic acid, dimethyl amide, polystyrene, maleate copolymer, etc., have been shown to act as asphaltene inhibitors. , Conventional methods of asphaltene content measurement and inhibitor selection utilize a large quantity of solvent, big glass vessels, and high temperature and pressure test methods and require qualified personnel for generating reliable data . Various methods have been developed for studying asphaltene precipitation and asphaltene deposition in conventional reservoirs, for example, microscopy, gravimetric analysis, viscosity measurement, filtration, electrical conductivity, light scattering, acoustic resonance, refractive index measurement, interfacial tension, heat transfer analysis, colloidal instability index, nuclear magnetic resonance, and gas chromatography coupled with mass spectrometry .…”
Section: Introductionmentioning
confidence: 99%